Spatial modeling of soil properties and its impact on investment The agricultural area parallel to the Shatt al-Arab (Journal of the College of Basic Education, 2022)
The research presented spatial modeling of soil properties and their impact on agricultural investment in the parallel area to the Shatt al-Arab, where the research problem represents the extent of physical and chemical matching of soil and international laws for its investment in agricultural spaces in the region. The study and geographical aspects in the typical work of ideal and imperfect agricultural investment for each element of the soil, and vice versa Its hypothesis is based on a clear match between the physical and chemical properties of the soil and the global print location. A spatial model for ideal and non-ideal agricultural investment for all soil elements and sets the goal of building a digital model It represents the spatial extension of ideal and non-ideal agricultural investment in the area parallel to the Shatt al-Arab, depending on geographic information systems. For agricultural investment in the eastern and southeastern part on the edge of the river and an area located